2005
DOI: 10.1002/pssc.200460465
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic pressure and spacer layer thickness effects on the optical properties of stacked InAs/InAlAs quantum dot array

Abstract: We report on investigations of InAs/InAlAs/InP stacked quantum dots (QDs). The photoluminescence spectroscopy (PL) and time resolved photoluminescence spectroscopy (TRPL) results, have shown an increase of the radiative life time and an important red shift of the PL band with decreasing the spacer layer thickness. The observed effects are explained as a consequence of the electronic coupling between vertical ordered QIs. The PL results have also shown that the emission from these structures depends not only up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…If the self-filtering effect is towards small (large) sizes a blue (red) shift of the photoluminescence (PL) spectrum is measured [6][7][8][9], whereas a redshift of the PL spectrum is observed when the electronic coupling increases [2,7,11,12]. A simultaneous and more important consequence of such electronic coupling is the exciton wavefunction delocalization along the growth direction [6,11,[14][15][16][17]. The properties of laser diodes based on this kind of stacked layers can be negatively modified by the above-described effects.…”
Section: Introductionmentioning
confidence: 99%
“…If the self-filtering effect is towards small (large) sizes a blue (red) shift of the photoluminescence (PL) spectrum is measured [6][7][8][9], whereas a redshift of the PL spectrum is observed when the electronic coupling increases [2,7,11,12]. A simultaneous and more important consequence of such electronic coupling is the exciton wavefunction delocalization along the growth direction [6,11,[14][15][16][17]. The properties of laser diodes based on this kind of stacked layers can be negatively modified by the above-described effects.…”
Section: Introductionmentioning
confidence: 99%
“…Photoluminescence studies of self-organized InAlAs/AlGaAs quantum dots under pressure were carried out by Phillips et al (1999). Recently, Hjiri et al (2005) reported the pressure effect on Photoluminescence…”
mentioning
confidence: 99%